A Perceptual Pathway to Bias: Interracial Exposure Reduces Abrupt Shifts in Real-Time Race Perception That Predict Mixed-Race Bias. (April 2016) - Freeman, Jonathan B.; Pauker, Kristin; Sanchez, Diana T.
In two national samples, we examined the influence of interracial exposure in one's local environment on the dynamic process underlying race perception and its evaluative consequences. Using a mouse-tracking paradigm, we found in Study 1 that White individuals with low interracial exposure exhibited a unique effect of abrupt, unstable White-Black category shifting during real-time perception of mixed-race faces, consistent with predictions from a neural-dynamic model of social categorization and computational simulations. In Study 2, this shifting effect was replicated and shown to predict a trust bias against mixed-race individuals and to mediate the effect of low interracial exposure on that trust bias. Taken together, the findings demonstrate that interracial exposure shapes the dynamics through which racial categories activate and resolve during real-time perceptions, and these initial perceptual dynamics, in turn, may help drive evaluative biases against mixed-race individuals. Thus, lower-level perceptual aspects of encounters with racial ambiguity may serve as a foundation for mixed-race prejudice.